Efficacy and Safety of High-Density Lipoprotein/Apolipoprotein A1 Replacement Therapy in Humans and Mice With Atherosclerosis: A Systematic Review and Meta-Analysis - Abudukeremu, Ayiguli; Huang, Canxia; Li, Hongwei; Sun, Runlu; Liu, Xiao; Wu, Xiaoying; Xie, Xiangkun; Huang, Jingjing; Zhang, Jie; Bao, Jinlan; Zhang, Yuling (Frontiers in Cardiovascular Medicine, 2021)
Background: Although elevation of HDL-C levels by pharmaceutical drugs have not benefit of cardiovascular endpoint, the effect of high-density lipoprotein/apolipoprotein A1 (HDL/apoA-1) replacement therapy on atherosclerosis is controversial. The current meta-analysis analyzed the effects of HDL/apoA-1 replacement therapies on atherosclerotic lesions both in humans and mice. Methods: The PubMed, Cochrane Library, Web of Science and EMBASE databases were searched through June 6, 2020. The methodological quality of the human studies was assessed using Review Manager (RevMan, version 5.3.). The methodological quality of the mouse studies was assessed using a stair list. STATA (version 14.0) was used to perform all statistical analyses. Results: Fifteen randomized controlled human trials and 17 animal studies were included. The pooled results showed that HDL/apoA-1 replacement therapy use did not significantly decrease the percent atheroma volume (p=0.766) or total atheroma volume (p=0.510) in acute coronary syndrome (ACS) patients (N=754). However, HDL/apoA-1 replacement therapies were significantly associated with the final percent lesion area, final lesion area and changes in lesion area (SMD, -1.75; 95% CI: -2.21 -1.29, p=0.000; SMD, -0.78; 95% CI: -1.18 -0.38, p=0.000; SMD: -2.06; 95% CI, -3.92 -0.2, p=0.03, respectively) in mice. Conclusions: HDL/apoA-1 replacement therapies are safe but do not significantly improve arterial atheroma volume in humans. The results in animals suggest that HDL/apoA-1 replacement therapies decrease the lesion area. Additional studies are needed to investigate and explain the differences in HDL/apoA-1 replacement therapy efficacies between humans and animals.